Security monitoring system of intelligent substation based on IoT - Yeshen HE; Kun LIANG; Wei TAN; Xin HU (Dianxin kexue)
Through the deployment of the internet of things,such as intelligent terminal,sensing sensor etc.,in the intelligent substation,a scene awareness mechanism was established under the mixed conditions to intelligent functions,such as the smart sensing of substation environment,infrastructure support,personnel exchanges,abnormal conditions judgments and other factors,and the multi-dimensional depth perception was realized.Meanwhile,interoperability of the perception network,the establishment of intelligent substation security monitoring system could be achieved by using wired and wireless fusion of multi-state communication technology.The system can multi-dimensionally perceive and monitoring the security of substation environment,which effectively enhances the smart substation intelligent monitoring level to ensure safe and stable operation of the substation.